Determinism and chaos - a story about Big Bang, singularity and the future of mankind - Alexandru Dinu; Madalin Frunzete (Annals of Mathematics and Physics - Peertechz Publications, 2023)
People have always tried to understand and tame the nature around them. It is a well-known fact that the sanest and safe approach from a psychological point of view is to focus on the present moment, the here and now. Nevertheless, we keep looking and living in the past or daydreaming and making predictions about what the future will bring. This paper is looking at this topic trying to unify several perspectives, stemming from a very diverse set of disciplines: biology, genetics, economics and cryptography, which are apparently working in parallel to solve the same problem. They all aim to find a theory of everything, one that can make sense out of chaos, light out of darkness and that can accurately predict the future based on present and past events. The current paper is supposed to inspire researchers to ask themselves tough questions, sometimes completely outside of their comfort zone, that can lead to discoveries with a huge positive impact on us all.